Simultaneous X‐ray fluorescence and scanning X‐ray diffraction microscopy at the Australian Synchrotron XFM beamline. (12th August 2016) - Jones, Michael W. M.; Phillips, Nicholas W.; van Riessen, Grant A.; Abbey, Brian; Vine, David J.; Nashed, Youssef S. G.; Mudie, Stephen T.; Afshar, Nader; Kirkham, Robin; Chen, Bo; Balaur, Eugeniu; de Jonge, Martin D.
Abstract : In both step‐ and fly‐scanning modes, robust, simultaneous XFM–SXDM (X‐ray fluorescence microscopy–scanning X‐ray diffraction microscopy) at the Australian Synchrotron XFM beamline is demonstrated. Using the fast‐scanning Maia detector system, robust, event‐mode SXDM data organization allows rapid imaging of large samples to be routine. Abstract : Owing to its extreme sensitivity, quantitative mapping of elemental distributions via X‐ray fluorescence microscopy (XFM) has become a key microanalytical technique. The recent realisation of scanning X‐ray diffraction microscopy (SXDM) meanwhile provides an avenue for quantitative super‐resolved ultra‐structural visualization. The similarity of their experimental geometries indicates excellent prospects for simultaneous acquisition. Here, in both step‐ and fly‐scanning modes, robust, simultaneous XFM‐SXDM is demonstrated.